ANALISIS POTENSI BRIKET BIO-ARANG SEBAGAI SUMBER ENERGI TERBARUKAN - Widya Fitriana; Wetri Febrina (The University of Lampung, 2021)
The research aimed to examine the potential of bio-charcoal briquettes as solid fuel using a SWOT analysis approach, by comparing them with non-briquette solid fuels. The SWOT method examines internal factors (IFAS) and external factors (EFAS). The research was conducted at a wood charcoal produces located at Dumai City, Riau. Data retrieval was carried out by means of observation and interview with the owner and workers. Including production data, marketing, problems faced during production, promotion and sale, product added value, product shortages and weaknesses, competitor data and opportunities in business development. The results of this research indicated that the advantages of briquette products was renewable, cheap, raw materials environmentally friendly, ease of packaging, cleanliness in the production process and efficiency in transportation. The disadvetages was less popular, requires a combustion furnace and fluctuating heat. The ooportunity was that the need for charcoal continues to increase, especially for restaurants and micro small industry. This research was recommend the importance of public policies related to the promotion and socialization of the use of bio-charcoal briquettes as a source of clean energy that is economical and environmentally friendly. Keywords: bio-charcoal briquettes, renewable energy, SWOT analysis